Ethics as scales of forms - Allen, R. T. (Studies in theoretical and applied ethics series., 2014)
This book is an important contribution to moral philosophy, and also to moral theology. It overcomes the dichotomising fragmentation of much contemporary moral philosophy which tends to take one aspect or component of moral activity, such as the consequences of actions, rules or intentions, and to make it the only one. The book employs an adaptation of Collingwood's scheme of 'scales of forms' to provide a synthesis which does justice to all aspects and components by placing each aspect, or c ...